Inovasi dalam Layanan Perbankan Berbasis Internet of Things (IOT) Peluang dan Tantangan di Era Digital - Siti Epa Hardiyanti (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The development of the Internet of Things (IoT) has changed the paradigm of banking services by offering innovations in operational efficiency, security and customer experience. Despite this, IoT implementation in the banking sector faces significant challenges related to data security and infrastructure costs. This research aims to explore the impact of implementing IoT in banking services and to identify the opportunities and challenges faced in the current digital era. This research method involves case studies, in-depth interviews, and surveys to analyze the use of smart ATMs, wearable devices, security sensors, and smart queuing systems in various banking contexts. The analysis results show significant improvements in operational efficiency and customer satisfaction, while also highlighting challenges related to data security and implementation costs. The implications of this research include recommendations for further development in IoT technology in banking services, with a focus on enhanced data security and effective implementation strategies.